2019
DOI: 10.1038/s41467-019-11235-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired lipoproteins-mediated photothermia remodels tumor stroma to improve cancer cell accessibility of second nanoparticles

Abstract: The tumor stromal microenvironments (TSM) including stromal cells and extracellular matrix (ECM) form an abominable barrier hampering nanoparticles accessibility to cancer cells, significantly compromising their antitumor effects. Herein, we report a bioinspired lipoprotein (bLP) that can induce efficient photothermia to remodel TSM and improve second bLP accessibility to cancer cells for antitumor therapy. The multiple stromal cells and ECM components in TSM are remarkably disrupted by bLP-mediated phototherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 63 publications
1
75
0
Order By: Relevance
“…Breast cancer cells are well known to overexpress CD44 proteins. Recently, Tao et al reported that SR-B1 is also expressed on breast cancer cells 26 . Previously, we developed an HPPS nanoparticle with strong SR-B1 targeting ability 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer cells are well known to overexpress CD44 proteins. Recently, Tao et al reported that SR-B1 is also expressed on breast cancer cells 26 . Previously, we developed an HPPS nanoparticle with strong SR-B1 targeting ability 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we developed a high-density lipoprotein (HDL)-mimicking peptide–phospholipid scaffold (HPPS) with hydrodynamic diameters of 10–30 nm 24 that can migrate to LNs by size-dependent passive transport 21 , 25 . Moreover, HPPS nanoparticles can target scavenger receptor class B type 1 (SR-B1), which is expressed on breast cancer cells 26 . Herein, we developed a novel dual-targeting nanoparticle by inserting the negatively charged HA-1,2-dimyristoyl phosphatidylethanolamine (DMPE) into a single-layer phospholipid of HPPS, denoted HA-HPPS.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies use magnetic NPs 63 or AuNPs 64,65 , which are simple to use, in biomarker detection assays, thereby saving time and money if compared with existing methods that require substantial sample processing. In addition to diagnostic screening, some therapeutic applications of NPs aim to remodel the tumour microenvironment to promote particle accumulation and penetration, and thus increase drug efficacy, and/or to sensitize tumours to a particular therapy [66][67][68] . For example, tumour-associated endothelial cells can be manipulated by a NP-delivered microRNA, which alters the tumour vasculature and thereby sensitizes the tumour to traditional cancer therapies 67 .…”
Section: Nps In Precision Medicinementioning
confidence: 99%
“…27 Therefore, the DOX-loaded nanoparticles we developed can enhance the ICD effect at a tumor site specifically. Moreover, tumor microenvironment remodeling mediated by photothermal therapy increases the accessibility of nanoparticles to tumor cells, 19 which undoubtedly amplifies the antitumor and ICD effect brought by DOX. However, we only developed a BT474 breast cancer cell nude mice model, and lacked a BT474/Adr breast cancer model.…”
Section: Dovepressmentioning
confidence: 99%